EFFORTS INCREASING POSITIVE CONFORMITY USING GROUP GUIDANCE SERVICES FOR JUNIOR HIGH SCHOOL STUDENTS OF CLASS VIII 1 TULANG BAWANG TENGAH DISTRICT TULANG BAWANG BARAT SCHOOL YEAR 2011/2012 - Tubagus Chandra; Yusmansyah Yusmansyah; Ranni Rahmayanthi (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research is to improve students' conformity to peers using group counseling services. The problem in this study is a positive conformity of students in low peers. Formulation of the problem in this study is whether the positive conformity students peers can be enhanced by using group counseling services..This study uses quasi-experimental design with one group Pretest and Posttest. Data collection techniques using positive conformity scale. Subjects in this study were 7 students who have low positive conformity. By calculation between pretest and posttest scores obtained ratio 89.42 pretest scores and posttest scores late 148.42 which means an increase of 59.14. This proves positive conformity increased by using group guidance services to students of class VII SMP Negeri 1 Tulang Bawang Tengah, Tulang Bawang Barat District School Year 2011/2012. The conclusion of this study is positive conformity student peers can be increased by using group counseling services. Suggestions proposed research are: (1) The student should be able to choose friendship that deserves to be followed. With the look and the positive and negative impacts for themselves it will be a great asset for the students to pass a good adolescence and achievement. (2) To the researchers, should be able to conduct research using a variety of service models and approaches in guidance in improving students' positive conformity to peers. (3) To the counseling teacher should be able to use the counseling services and a variety of other approaches to direct conformity phenomenon that occurs in students, so that students' progress can thrive.Keywords : group-guidance service, conformity positive